Alcohol withdrawal delirium - diagnosis, course and treatment - Mainerová, Barbora; Praško, Ján; Látalová, Klára; Axmann, Karel; Černá, Monika; Horáček, Rostislav; Bradacova, Romana (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2015)
OBJECTIVE: Delirium tremens represents the most severe complication of alcohol withdrawal syndrome and, in its complications, significantly increases the morbidity and mortality of patients. Alcohol withdrawal delirium is characterized by features of alcohol withdrawal itself (tremor, sweating, hypertension, tachycardia etc.) together with general delirious symptoms such as clouded consciousness, disorientation, disturbed circadian rhythms, thought processe and sensory disturbances, all of them fluctuating in time. The treatment combines a supportive and symptomatic approach. Benzodiazepines in supramaximal doses are usually used as drugs of choice but in some countries such as the Czech Republic or Germany, clomethiazole is frequently used as well. METHOD: A computer search of the all the literature published between 1966 and December 2012 was accomplished on MEDLINE and Web of Science with the key words "delirium tremens", "alcohol withdrawal", "treatment" and "pharmacotherapy". There were no language or time limits applied. CONCLUSIONS: When not early recognized and treated adequately, delirium tremens may result in death due to malignant arrhythmia, respiratory arrest, sepsis, severe electrolyte disturbance or prolonged seizures and subsequent trauma. Owing to these possible fatalities and other severe unexpected complications, delirium tremens should be managed at an ICU or wards ensuring vital signs monitoring. In symptomatic treatment, high doses of benzodiazepines, especially lorazepam, diazepam and oxazepam are considered the gold standard drugs. Supportive therapy is also of great importance.
Keywords: Benzodiazepines; Alcohol Withdrawal Delirium; Disease Management; lidé; alkoholové delirium; Humans; management nemoci; Psychometrics; psychometrie; benzodiazepiny